Brand Perception Pada Purchase Decision Melintasi Purchase Interest Produk RTD Teh Merek Pucuk Harum Di Masyarakat Kota Kediri - Hery Purnomo; Samari Samari; Dodi Kusuma Hadi Soejoko (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2022)
The research aims to measure how much the relationship of brand awareness, brand trust and brand personality crosses purchase interest in Purchase Decision RTD Tea Merek Pucuk Harum in Kediri City community. The research used a quantitative approach, and sampled 100 respondents, with stratified random sampling techniques on a proposional basis. Testing data with primer using Multiple linear regression. The study found that on a direct trajectory, brand awareness has a significant relationship with purchase interest, but not on brand trust and brand personality. While brand awareness, brand trust or brand personality has no significant relationship with purchase decisions. On an indirect trajectory, brand Awareness has a significant relationship with purchase decisions, through purchase interest, while brand trust and brand personality do not have a relationship meaning in creating purchase decisions across purchase interest as mediation variables. The diversity of data described by the model is 35%, the rest is explained by other variables that are not yet in the model and errors.